Draft Genome Sequence of the Haloacid-Degrading Burkholderia caribensis Strain MBA4 - Pan, Yanling (American Society for Microbiology, 2014)
Burkholderia caribensis MBA4 was isolated from soil for its ability to utilize 2-haloacid. An inducible haloacid operon, encoding a dehalogenase and a permease, is mainly responsible for the biotransformation. Here, we report the draft genome sequence of this strain.